Causal mechanism and explanation in social science - Renate Mayntz (Max Planck Institute for the Study of Societies, 2020)
In the social sciences, the development of a specific social event or structure is often explained by a statistical correlation between an independent variable and a variable assumed to be dependent upon it. This mode of explanation is contested by a methodology of causal reconstruction that operates with the concept of mechanisms. A mechanism is a process in which a set of linked steps leads from initial conditions to an outcome or effect. Mechanisms are general concepts, subjecting individual cases to a general category. Except for the literature dealing specifically with the concept, the term 'mechanism' is often used without definition of its substantive content; there is no agreement with respect to the unique or plural character of the initial conditions, nor to the structure of the causal path leading to a specific outcome. Nevertheless, mechanisms have played a crucial role in detailed causal analysis of complex historical events, such as the financial crisis of 2008 and German unification of 1989. – – Das Zustandekommen eines sozialen Phänomens wird häufig durch eine statistische Korrelation zwischen einer unabhängigen und einer vermutlich davon abhängigen Variable erklärt. Demgegenüber verlangt die mit dem Begriff von Mechanismen operierende kausale Rekonstruktion eine Erklärung durch einen Prozess, in dem eine Reihe verbundener Schritte von spezifischen Ausgangsbedingungen zu einem Ergebnis führt. Mechanismen sind Allgemeinbegriffe, denen konkrete Einzelfälle zugeordnet werden. Abgesehen von einer Literatur, die sich ausdrücklich mit dem Konzept beschäftigt, wird der Begriff Mechanismus oft ohne Hinweis auf seinen Inhalt benutzt; dazu gehört die einfache oder plurale Natur der Anfangsbedingungen oder die Struktur des zum Ergebnis führenden kausalen Pfades. Trotzdem spielen als Mechanismen bezeichnete Prozesse eine wichtige Rolle bei der Erklärung komplexer historischer Ereignisse wie der Finanzkrise von 2008 und der deutschen Vereinigung von 1989.
hdl:21.11116/0000-0006-54B8-C
Keywords: 300; causal reconstruction; finance crisis; German unification; mechanism; deutsche Vereinigung; Finanzkrise; kausale Rekonstruktion; Mechanismen